“Chapter 13”: The Political Value of Emotions - Silva, Laura (Les ateliers de l'éthique / The Ethics Forum)

(untitled) (Centre de recherche en éthique (CRÉ), 2024)
Christine Tappolet had plans to include a thirteenth chapter, on the political value of emotions. As the chapter did not come to fruition, at least not in the current edition, I will here outline what I take to be the main political upshots of Tappolet’s philosophy of emotion.